Non-Surgical Devices for Nasal Obstruction - Deot, Neal; Obayemi, Adetokunbo; Davila, Richard O. (Facial Plastic Surgery, 2022)
Nasal obstruction is a common presenting complaint in most otolaryngology practices. A reduction of nasal airflow can contribute to exercise intolerance, snoring, obstructive sleep apnea (OSA), and an overall decreased quality of life. When medical management for non-anatomical issues fails to resolve the obstruction, surgeries targeting nasal obstruction—namely septorhinoplasty and/or inferior turbinate reduction are often considered. A frequently overlooked alternative for these patients is the wide array of non-surgical and minimally invasive appliances available to address nasal obstruction. This article attempts to provide a basic overview of these devices, benefits, and limitations, and the evidence supporting their efficacy in alleviating nasal obstruction.
Keywords: nasal obstruction; nasal cone; nasal stent; septorhinoplasty; nasal appliance